(untitled) (Iranian Journal of Kidney Diseases, 2017)
Treatment of snakebite complications is challenging, as it is difficult to distinguish what kind of antivenins should be used. Kidney failure as a result of rhabdomyolysis or hemolysis may happen due to accumulated fluids that increase the pressure in the abdomen. This case report describes acute kidney failure probably due to intra-abdominal hypertension following an unknown bite.